Employing Model Based Conceptual Design to Identify Test Range Resources Required to Validate the Delivered Solution. Issue 1 (30th September 2020) - Flanigan, David; Robinson, Kevin
Abstract: During an initial system concept development, systems engineers will look at different areas of the problem space in order to develop a solution that will satisfy the overall capabilities defined by the stakeholders. During this phase, the problem space is intentionally left large in order to consider a larger scope of the solution space and operational environment. Thus, the SE would like to consider as much of the space as possible to determine what is feasible and infeasible when progressing on to the next phase of system development. This paper reports on an extension of Model Based Conceptual Design (MBCD) that visualizes the potential feasible solution space in order to inform decision makers of feasible solutions and test range resources required to validate the delivered solution. An approach is offered, utilizing Design of Experiments methods, to extend previous research on test and evaluation with MBCD as applied to an illustrative use case.